2019
DOI: 10.1007/s00330-019-06244-2
|View full text |Cite|
|
Sign up to set email alerts
|

Machine learning classifiers can predict Gleason pattern 4 prostate cancer with greater accuracy than experienced radiologists

Abstract: Objective The purpose of this study was: To test whether machine learning classifiers for transition zone (TZ) and peripheral zone (PZ) can correctly classify prostate tumors into those with/without a Gleason 4 component, and to compare the performance of the best performing classifiers against the opinion of three board-certified radiologists. Methods A retrospective analysis of prospectively acquired data was performed at a single center between 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
3
55
0
Order By: Relevance
“…The flow diagram is depicted in Figure 1 . In total, 27 articles were eligible for inclusion in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. From these, 13 studies reported enough information to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram is depicted in Figure 1 . In total, 27 articles were eligible for inclusion in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. From these, 13 studies reported enough information to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies outlined the potential of radiomics for PCa characterization in mpMR images. Antonelli et al [ 18 ] found that zone-specific models combining PSAD and radiomic features outperformed experienced radiologist assessments for the csPCa detection. Chaddad et al [ 23 ] found a significant correlation between GLCM features extracted jointly from T2w and ADC images and Gleason score, with an AUC of 0.78 for GS ≤ 3, 0.82 for GS 3+4 and 0.65 for GS ≥ 4+3.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzed image features include shape features, first-order statistics, and texture characteristics, such as grey level co-occurrence matrices (GLCM) [ 16 ]. Recent advances in image analysis techniques using radiomic features to assess genomic, proteomic, and clinical phenotypes of the prostate tumor were shown to match or even surpass the qualitative imaging assessment of radiologists [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…2) With regard to specific cut-off value based diagnosis, diagnostic models such as logistic regression, support vector machine, K nearest neighbor and so on are much better at classifying. 19,21 Previous research has demonstrated the clinical potential of mono-exponential DWI or histogram analysis in evaluating the therapeutic response of HCC (for example: TACE or other novel targeted therapies) 22 and diagnostic value in combination with LI-RADS. 23,25 However, hardly ever were IVIM-derived histogram metrics applied for addressing the above issues.…”
Section: Diagnostic Performance Analysismentioning
confidence: 99%